The Impact of Skills Training and Access to Financial Services on the Development of Young Farmers' Entrepreneurial Capacity in Pucanglaban District - Putri, Apria Yuvitar Devani; Winarno, Sri Tjondro; Setiawan, Risqi Firdaus (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
A sharp decline of 7.45% in the number of farmers occurred over the decade from 2013 to 2023, accompanied by slowing regeneration among young farmers. In response to this challenge, the Ministry of Agriculture collaborated with the International Fund for Agricultural Development (IFAD) to initiate the Youth Entrepreneurship and Employment Support Services (YESS) Program, aimed at fostering agricultural regeneration by enhancing youth entrepreneurship capacity in the agricultural sector. This study analyzes the influence of skills training and financial service access on the entrepreneurial capacity of young farmers in the YESS Program. The research sample was determined using cluster random sampling, involving 79 young farmers in Pucanglaban District, with data collected through questionnaires during January-February 2025. Employing a descriptive quantitative method, the study applied Structural Equation Modeling (SEM) using WarpPLS 8.0. The results indicate that skills training and financial service access have a positive and significant impact on young farmers' entrepreneurial capacity. This study reinforces the importance of providing skills training and financial access to young farmers as a strategy to promote youth agripreneurship .